Mercury Adsorption Test on Several Large Groups of Soils in West Sumbawa Regency, Indonesia - Hapsari Hurum, Puji; Kusnarta, IGM; Sarjan, M.; Suwardji, Suwardji (Publisher Cv. Inara, 2024)
Mercury is one of the heavy metals that has the highest toxicity in the global environment. Mercury can cause environmental damage and if it enters the food chain it can have negative impacts on human health. In overcoming the problem of mercury entering the food chain, it is very important to study the mobility and distribution of mercury in the soil. The presence of mercury (Hg2+) in soil is largely controlled by adsorption reactions with certain specific adsorption patterns. Therefore, it is very important to study mercury adsorption on several different types of soil in order to get an idea of ??how adsorption occurs in West Sumbawa Regency. The aim of this research is to determine the pattern and capacity of mercury adsorption on various large groups of soil in West Sumbawa Regency and the relationship between soil properties and mercury adsorption. The results of the research show that the adsorption isotherm pattern in the great soil groups Endoaquepts, Ustipsamments, and Udorthents more closely follows the Langmuir adsorption model, while the great soil groups Haplustepts, Hapludolls, Eutrudepts and Ustifluvents follow the Freundlich adsorption model. The major soil group that has the highest maximum mercury adsorption capacity in West Sumbawa Regency is Endoaquepts at 4,604 mg/g.